Effects of high neutron fluence on the electrical characteristics of InAs quantum dot structures - Ahmad Fauzi, Dhiyauddin; Alang Md Rashid, Nahrul Khair; ., Md. Rashid; Che Omar, Nuurul Iffah; Hasbullah, Nurul Fadzlin; Mohamed Zin, muhammad Rawi (2013)
The use of InAs quantum dots (QDs) in a well (DWELL) structure as a medium to minimize propagation of neutron induced defects is presented. The DWELL samples and GaAs based commercial diodes were radiated with thermal neutron under maximum fluence of 1.4×1016 neutron/cm2. Based on the current-voltage (I-V) characteristics, it was discovered that the forward bias (FB) leakage current for both devices decreased as an effect of increment in series resistance. In reverse bias (RB), there is significant decrement in leakage current of DWELL samples in the order of 2 orders of magnitude. The RB leakage current of GaAs diode showed similar response as in FB. However, the QD based structures showed less defects compared to the GaAs based diodes